Evolutionary characterization of lung cancer metastasis - Sonya Hessey; Abigail Bunkum; Ariana Huebner; Kerstin Haase; Kristiana Grigoriadis; Cristina Naceur-Lombardelli; Wing Kin Liu; Caitlin F. Harrigan; Charlotte Grieco; Daniele Marinelli; Boyue Ding; Carlos Martínez-Ruiz; et al. (Nature, 2026)
Abstract Limited understanding of the biological processes that govern metastatic dissemination hinders its prevention and treatment 1 . Here, using 501 longitudinally collected primary and metastatic tumour samples from 24 patients with non-small cell lung cancer (NSCLC) enrolled in the TRACERx lung study and PEACE autopsy programme, we infer tumour evolution from diagnosis to death. With DNA-sequencing data encompassing 70% of the metastases that were radiologically detected before death and paired multi-region sampled primary tumours, we show that the genomes of metastases diverge markedly from those of their ancestral primary tumour, with additional driver alterations and genome doubling events occurring after metastatic dissemination. In 62.5% of patients, multiple primary tumour subclones disseminated, each founding a distinct metastasis. These metastases served as sources of onward spread: more than half of the metastases sampled were seeded by other metastases. The duration that metastases existed in situ influenced their likelihood of seeding further metastases. Most metastatic migrations started and ended in the same anatomical cavity. The few subclones that exited the thorax to seed metastases disseminated widely and were enriched for somatic copy-number alterations, suggesting that chromosomal instability may facilitate extrathoracic spread. This spatial and temporal evolutionary analysis sheds light on the extent of metastatic diversity and seeding in advanced NSCLC—which tends to be underestimated in single metastasis biopsies—and identifies genomic and clinical mediators of metastatic progression.